Authentic Happiness, Organizational Politics, and Career Transition Among Public Secondary School Teachers: A Convergent Design - Tubo, Mariane; J. Pidor, Sylvia (The Future of Education Journal, 2025)
This study determined the influence of authentic happiness and organizational politics on career transition of public secondary school teachers in Region XI. This study utilized mixed methods research particularly convergent design. In the quantitative phase, adapted and validated survey questionnaires were employed while an interview guide was utilized in the qualitative phase during in-depth interview and focus group discussion. The statistical tools used in analyzing the quantitative data included mean, standard deviation, and multiple linear regression analysis while thematic analysis was used for the qualitative data. The results revealed that the status of authentic happiness, organizational politics and career transition were rated high. Further, authentic happiness and organizational politics significantly influenced career transition. Furthermore, the themes generated from the lived experiences of teachers were the following: driven by dissatisfaction, financial security, career sustainability, and health awareness. The themes extracted from the role of experiences that shaped their beliefs included fulfillment of goals in life and disadvantageous outcomes of teaching workplace stressors. Likewise, diminishing ethical standards of professional teachers and unfavorable display of behavior were the themes generated from the experiences that shaped their attitude. The nature of data integration revealed merging-converging.